OBJECTIVES, CAPACITIES OR COMPETENCES? - Tacca Huamán, Daniel (2014)
In these times of constant changes, the education sector is not free to vary its paradigms and terms. Objectives (goal, purpose), capacities and competences are words (terms) that involve a trouble (confusion, misunderstanding), when determining its sense and its daily usage. This work will develop a proposal to clearly define their meaning and to point out the differences between these.